Genetic individual identification from dried urine spots: A complementary tool to drug monitoring and anti‐doping testing. Issue 7 (28th February 2022) - Grignani, Pierangela; Manfredi, Alessandro; Monti, Maria Cristina; Moretti, Matteo; Morini, Luca; Visonà, Silvia Damiana; Fattorini, Paolo; Previderè, Carlo
Abstract: The collection of liquid biological matrices onto paper cards (dried matrix spots [DMS]) is becoming an alternative sampling strategy. The stability over time of molecules of interest for therapeutic, sport drug monitoring, and forensic toxicology on DMS has been recently investigated representing a reliable alternative to conventional analytical techniques. When a tampering of a urine sample in drug monitoring or doping control cases is suspected, it could be relevant to know whether genetic profiles useful for individual identification could be generated from urine samples spotted onto paper (dried urine spot [DUS]). To understand the influence of sex, storage conditions, and time on the quality and quantity of the DNA, five female and ten male urine samples were dispensed onto Whatman 903 paper and sampled after different storage conditions over time, from 1 to 12 weeks. Direct PCR was performed starting from 2‐mm punches collected from each spot amplifying a panel of markers useful for individual identification. The female DUS stored in different conditions produced genetic profiles fully matching the reference samples. The same result was obtained for the male DUS but using urine 30X concentrated by centrifugation instead of the original samples. Our data show that this approach is valid for genetic individual identification of urine samples spotted onto paper cards up to 12 weeks after deposition and could be easily incorporated in anti‐doping or drug screening protocols to help on the suspicion of evidence tampering or to solve questions on the reliability of samples collection. Abstract : The results presented in this study show that it is possible to obtain profiles useful for genetic individual identification from dried urine spots (DUS) stored in different condition up to 12 weeks after deposition. The genetic profiles were achieved through direct PCR amplification of STR markers contained in a validated forensic kit.